2008
DOI: 10.1007/s11692-008-9016-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Placentation in Primates: Implications of Mammalian Phylogeny

Abstract: Primates are quite unique among placental mammals in that the two extreme types of placentation are present within a single order. Strepsirrhines (lemurs and lorisiforms) have non-invasive epitheliochorial placentation, whereas haplorhines (tarsiers and higher primates) have highly invasive haemochorial placentation. Resemblance in placenta type in fact provided the first evidence that tarsiers are linked to higher primates and distinct from lemurs and lorisiforms. Tree-shrews differ from both primate subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 82 publications
3
43
0
1
Order By: Relevance
“…Although it has been suggested that the structure of the placenta might influence nutrient transfer and hence prenatal brain growth (15,27), recent comparative studies find no evidence for a specific relationship between placental structure and brain growth (28,29). Capellini et al found that variation among mammals in placental structure correlated with fetal growth rates and gestation duration, but not with neonate brain size (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that the structure of the placenta might influence nutrient transfer and hence prenatal brain growth (15,27), recent comparative studies find no evidence for a specific relationship between placental structure and brain growth (28,29). Capellini et al found that variation among mammals in placental structure correlated with fetal growth rates and gestation duration, but not with neonate brain size (28).…”
Section: Discussionmentioning
confidence: 99%
“…Placental gross morphology varies in the number and position of the exchange areas over the placental surface (shape), in how maternal and fetal tissues are spatially arranged with one another (interdigitation), and in the number of maternal tissue layers separating maternal blood from fetal tissues (invasiveness ;Mossman 1987;Leiser and Kaufmann 1994;Wooding and Burton 2008). Placental invasiveness is the trait that has received the most attention regarding a possible impact of placental morphology on offspring prenatal development and maternal investment, particularly in relation to brain growth (Kihlström 1972;Sacher and Staffeldt 1974;Leutenegger 1979;Haig 1993;Crespi and Semeniuk 2004;Elliot and Crespi 2008;Martin 2008). In noninvasive epitheliochorial placentation, three maternal tissue layers (uterine epithelium, connective tissues, and endothelium) constitute a barrier between fetal tissues and maternal blood (Mossman 1987;Leiser and Kaufmann 1994;Wooding and Burton 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Haig (1993, p. 501) related placental invasiveness to maternal-fetal conflict, arguing that hemochorial placentation "evolved more than once as a means by which the fetus gained greater access to maternal nutrients." However, recent phylogenetic studies suggest that more invasive placentas (either hemochorial or endotheliochorial) are likely to be the ancestral condition for mammals, with the least invasive epitheliochorial placentation being an evolutionarily derived trait that emerged independently in several lineages (Vogel 2005;Mess and Carter 2006;Wildman et al 2006;Carter and Mess 2007;Martin 2008;Elliot and Crespi 2009). In a sense, therefore, it is the repeated evolution of less invasive placentas that is demanding of an explanation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That has been confirmed numerous times though there is disagreement about whether the plesiomorphic state is endotheliochorial (Mess and Carter, 2006;Martin, 2008) or haemochorial (Wildman et al, 2006;Elliot and Crespi, 2009). …”
Section: Interhaemal Barriermentioning
confidence: 90%